The Relation Between Empathy and Insight in Psychiatric Disorders: Phenomenological, Etiological, and Neuro-Functional Mechanisms - Thirioux, Bérangère; Harika-Germaneau, Ghina; Langbour, Nicolas; Jaafari, Nematollah (Frontiers in Psychiatry, 2020)
Lack of insight, i.e., unawareness of one’s mental illness, is encountered in psychiatric conditions. Insight is the capacity to recognize (psychical insight) and accept one’s mental illness (emotional insight). Insight growth necessitates developing an objective perspective on one’s subjective pathological experiences. Thus, insight has been posited to require undamaged self-reflexion and cognitive perspective-taking capacities. These enable patients to look objectively at themselves from the imagined perspective of someone else. Impaired Theory-of-Mind performances have been reported to negatively impact insight in psychosis. Moreover, some patients with schizophrenia or obsessive-compulsive disorders, although recognizing their mental disease, are not convinced of this and do not accept it. Hence, perspective-taking explains psychical insight (recognition) but not emotional insight (acceptance). Here, we propose a new conceptual model. We hypothesize that insight growth relies upon the association of intact self-reflexion and empathic capacities. Empathy (feeling into someone else) integrates heterocentered visuo-spatial perspective (feeling into), embodiment, affective (feeling into) and cognitive processes. It enables to internally experience the other’s thought. We posit that this subjective experience enables to better understand the other’s thought about oneself and to affectively adhere to this. We propose that the process of objectification, resulting from empathic heterocentered, embodiment and cognitive processes, generates an objective viewpoint on oneself. It enables to recognize one’s mental illness and positively impacts psychical insight. The process of subjectification, resulting from empathic affective processes, would enable to accept one’s illness and positively impacts emotional insight. That is, affectively experiencing the thought of another person about oneself reinforces the adhesion of the emotional system to the objective recognition of the disease. Applying our model to different psychiatric disorders, we predict that the negative effect of impaired self-reflexion and empathic capacities on insight is a transnosographic state and that endophenotypical differences modulate this common state, determining a psychiatric disease as specific.